2005
DOI: 10.1111/j.0737-1209.2005.220503.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Work Stress and Family Stress to the Self‐Rated Health of Women Employed in the Industrial Sector in Korea

Abstract: Both work stress and family stress should be considered together when addressing the health of working women in the industrial sector in Korea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…Although a study of South Korean women revealed intense psychosomatic stress and job stress associated with having multiple roles (Kim et al, 2005), there is a desirable, social change in Iran taking place with regard to women's employment. Iranian women now have increased access to the full range of higher education opportunities and the full range of employment opportunities, leading to a reduction in gender inequality (Iranian Centre for Studies and Researches on Women, 2005).…”
Section: Employmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a study of South Korean women revealed intense psychosomatic stress and job stress associated with having multiple roles (Kim et al, 2005), there is a desirable, social change in Iran taking place with regard to women's employment. Iranian women now have increased access to the full range of higher education opportunities and the full range of employment opportunities, leading to a reduction in gender inequality (Iranian Centre for Studies and Researches on Women, 2005).…”
Section: Employmentmentioning
confidence: 99%
“…Investigators of the relationship between professional and family stress and the status of women's health in South Korea found a positive correlation between social support and health status, whereas they observed an inverse association between professional and family stress and state of health (Kim, Won, Chung, Lucy, & Kim, 2005).…”
mentioning
confidence: 99%
“…Chronic work stress, daily fluctuations in job demands, and work‐to‐family conflicts have been found to predict individuals’ negative moods, psychological symptoms, and health complaints (Bolger, DeLongis, Kessler, & Wethington, 1989; Jones & Fletcher, 1996; Windle & Dumenci, 1997). Similar harmful effects of work‐related stress on individuals’ well‐being have been identified in studies conducted worldwide (cf., Etzion & Westman, 2001; Kim, Cho, Lee, Marion, & Kim, 2005) and in cross‐national research (Spector et al, 2004), suggesting that the effect of work stressors on psychological well‐being and physical health is universal (Poelmans et al, 2003).…”
Section: The Effect Of Work Stress On Couple Relationshipsmentioning
confidence: 99%
“…The findings empirically confirm the arguments given by Kim, Cho,Lee,Marion and Kim(2005) and Luecken,Suarez,Kuhn ,Barefoot ,Blumental ,Siegler and Willams(2006) that married women proven more stress on their occupations than single women and also, family and marital responsibilities can be severely disrupted by shift work or long hours .Child care, housework, shopping and leaving a partner alone at night can all lead to marital strain and family dysfunction.…”
Section: Levels Of Job Stresssupporting
confidence: 85%